User satisfaction of the Nanyang Technological University Library - Cheong, Shermeen Woon Teng (2008)
This study investigates four aspects (online services, non-online services, printed materials and communication) of satisfaction level of users of NTU library. Respondents consisted of academic staff, research staff and research students. Findings showed that while overall, respondents were satisfied with most of the services, their satisfaction varied when analysed separately according to their sample characteristics.